“Kambakutaisoto” and Emotional Instability Associated With Premenstrual Syndrome - Shiota, Atsuko; Shime, Chika; Nakai, Kyoko; Kageyama, Mitsuru (Frontiers in Nutrition, 2021)
Many women suffer from premenstrual syndrome (PMS), which can be considered a modern illness in this busy society; mental symptoms, such as irritability, often affect the surroundings and result in loss of self-confidence. The symptoms of PMS are diverse, and it is often difficult to treat psychiatric and social symptoms with low-dose estrogen progestin combination drug (LEP) alone. Selective serotonin reuptake inhibitors (SSRIs) are also effective; however, many are unable to take them owing to their side effects. “Kambakutaisoto” is a Kampo medicine consisting of “jujube,” “licorice,” and “wheat,” which is often described as “food”; however, it is highly effective in treating emotional instability attributed to PMS in sensitive young women. There are many reports on the effects of kambakutaisoto; the molecular nutritional findings of kambakutaisoto, which has dramatic effects despite its mild composition of crude drugs, have also been reported, suggesting an association with premenstrual exacerbation of functional hypoglycemia. A narrative review of its clinical effects on PMS and the results of molecular nutrition studies was performed.